Media Interaktif Pembelajaran Sistem Peredaran Darah Manusia - Kwarrie, Yohanes Nicolas Paulo; Liliana, Liliana; Purba, Kristo Radion (Jurnal Infra, 2015)
Human circulatory system is a topic that is very important to be learned. But in the process to learn it, it takes a high level of understanding because it is difficult to say with verbal language. Processes that occur in it are difficult to observe, happened so fast or even too slow. One way to understand it is through multimedia.This application will resemble the human circulatory system more interactive and interesting, in which players actively involved in the learning process. Starting from blood, blood vessels, heart, circulatory, until disease. There is also a test to measure the ability of a user. This application is created using Adobe Flash Professional CS6.From the questionnaire result and human computer interaction test, prove that the simulation strongly supports the process of understanding the material. Therefore userâs interest in learning is increased, coupled with the easiness of application usage and user friendly.